Subjective and Objective Assessment of Taste and Smell Sensation in Advanced Cancer. (August 2019) - McGettigan, Niamh; Dhuibhir, Pauline Uí; Barrett, Michelle; Sui, Jessica; Balding, Lucy; Higgins, Stephen; O'Leary, Norma; Kennedy, Aileen; Walsh, Declan
Context: Taste and smell abnormalities (TSA) occur throughout the cancer trajectory regardless of cancer primary site and contribute to cancer-associated malnutrition. TSA etiology is poorly understood. Tumor-related inflammation is a possible cause. Objective: This study examined the prevalence, characteristics, and severity of TSA in advanced cancer and explored the relationship between TSA and nutritional status. No previous study combined subjective and objective measures for both taste and smell assessment in this population. Method: Consecutive advanced cancer hospice patients were recruited. A modified version of the "Taste and Smell Survey" assessed subjective TSA. Validated taste strips and "Sniffin' Sticks" were the objective measures. The abridged patient-generated subjective global assessment evaluated nutritional status. Results: A 93% prevalence of TSA in 30 patients with advanced cancer was identified. When subjective and objective evaluations were combined, 28 had taste abnormalities, 24 smell abnormalities, and 24 both. Taste changes included "persistent bad taste" (n = 18) and changes in how basic tastes were perceived. Half reported smell was not "as strong" as prediagnosis, while more than half (n = 16) had an objective smell abnormality. Most (97%) were at risk of malnutrition. Fatigue, dry mouth, early satiety, and anorexia were common nutrition-impact symptoms. No statistically significant relationship was found between TSA and malnutrition scores. Conclusions: TSA were highly prevalent. Subjective taste and smell changes did not always accord with objective TSA, suggesting both assessments are valuable. TSA characteristics varied, and particular foods tasted and smelled different and were not enjoyed as before. TSA are common, high-impact problems in advanced cancer.